Rapid quantification of the binocular visual field for clinical trials: performance of a modified Esterman supra-threshold test implemented with the open perimetry interface - Andrews, CD; Sheldon, AA; Bridge, H; Downes, SM; MacLaren, RE; Jolly, JK (Dove Press, 2022)
Purpose: We aimed to assess the performance of the modified-Esterman test (mET) as a rapid suprathreshold binocular quantification tool for the assessment of peripheral visual fields. The mET consists of an even spread of test points across the visual field. Materials and Methods: The mET was implemented on the Octopus 0900 perimeter using the Open Perimetry Interface (OPI) and consisted of 160 points. Patients with choroideremia, a rod-cone dystrophy, Stargardt disease, a cone-rod dystrophy, and healthy volunteers underwent both the mET and the standard Esterman tests twice. Disease severity (mild/moderate/severe) was graded on both tests independently. Voronoi tessellation was utilised to compare the tests. Results: The Voronoi visualisation was able to demonstrate that the mET was able to provide more information about the disease state at all stages of diseases. This was confirmed by the agreement statistic, which showed that the mET detected 27% more points of visual field loss compared to the Esterman test, being most useful in patients with rod-cone dystrophies. Conclusion: The mET provides a speedy quantitative measure of the peripheral visual field loss, which can be used in clinical trials to monitor longitudinal assessment of peripheral visual function. The mET provides a more even coverage across the visual field compared to the Esterman test points, making it more suitable for this purpose. This is a key part of safety monitoring in retinal clinical trials. The mET can easily be implemented on commercially available perimeters that allow Open Perimetry.